REPRESI TERHADAP KEBEBASAN AKADEMIK DALAM POLITIK ELEKTORAL INDONESIA - Herlambang P. Wiratraman (Veritas et Justitia, 2025)
The relationship between campuses and political power continues to be shaped by partisan interests. Increasing politicization reflects the strategic importance of campus life as an object of discipline, co-optation, and control within broader power structures. This dynamic was evident during the 2024 Indonesian elections, both at the presidential and regional levels. This article analyzes patterns observed in these elections, which featured multiple instances of political pressure exerted through state apparatuses seeking to mobilize campuses in support of the Joko Widodo administration through various manipulative strategies. Existing studies have paid limited, if any, attention to the position of campuses and electoral processes from the perspective of academic freedom, particularly within legal analysis focused on its practical application. This article therefore asks why academic freedom becomes particularly vulnerable during electoral periods and why campuses appear especially susceptible to political pressure in such contexts. Employing an interdisciplinary law-and-society approach, the article argues that the subordination of campuses during elections is neither incidental nor novel. Rather, campuses have been repeatedly sacrificed in electoral politics and are increasingly subject to systematic co-optation through policy instruments that constrain and neutralize their critical function.